Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18203/2319-2003.ijbcp20161549
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of glipizide and fenugreek (Trigonella foenum-graecum) seeds as monotherapy and combination therapy on glycaemic control and lipid profile in patients with type 2 diabetes mellitus

Abstract: Background: Diabetes is commonly associated with dyslipidemia, which is one of the major risk factors of coronary heart disease (CHD), the leading cause of mortality in patients with type 2 diabetic. It is thus desirable that an anti-diabetic drug must provide good glycaemic control and in addition cause correction of dyslipidaemia, at the same time being safe. Fenugreek, a traditional drug has been found to have beneficial effect on glycaemic control as well as lipid profile and may be thus useful in such pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(44 reference statements)
2
8
0
Order By: Relevance
“…Trigonella foenum-graecum significantly reduced HbA1c (−0.6%; −0.9 to −0.4), FBG (−14 mg/dl; −22 to −5), PPBG (−21 mg/dl; −34 to −7), stimulated insulin (as insulin sensitizer; −21 mIU/L; −36 to −5), fasting C-peptide (as insulin sensitizer; −0.41 ng/ml; −0.67 to −0.16), BMI (−0.6 kg/m 2 ; −1.1 to −0.1), waist circumference (−4 cm; −7 to −1), and TG (−23 mg/dl; −46 to −1), and increased stimulated C-peptide (as insulin sensitizer; 0.93 ng/ml; 0.09–1.77) (see Figure 33 ). ( Gupta et al, 2001 ; Lu et al, 2008 ; Yaheya and Ismail, 2009 ; Ansari et al, 2011 ; Rafraf et al, 2014 ; Suchitra and Parthasarathy, 2015 ; Kaur et al, 2016 ; Singh et al, 2016 ; Verma et al, 2016 ; Ranade and Mudgalkar, 2017 ; Gholaman and Gholami, 2018 ; Kandhare et al, 2018 ; Hassani et al, 2019 ; Hota et al, 2019 ; Rashid et al, 2019 ; Hadi et al, 2020 ) Publication bias was detected in the funnel plot for HbA1c but not for FBG. In the funnel plot for HbA1c, there was an absence of smaller sized studies showing a larger positive effect, which could imply the effect may be larger than that reported from the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trigonella foenum-graecum significantly reduced HbA1c (−0.6%; −0.9 to −0.4), FBG (−14 mg/dl; −22 to −5), PPBG (−21 mg/dl; −34 to −7), stimulated insulin (as insulin sensitizer; −21 mIU/L; −36 to −5), fasting C-peptide (as insulin sensitizer; −0.41 ng/ml; −0.67 to −0.16), BMI (−0.6 kg/m 2 ; −1.1 to −0.1), waist circumference (−4 cm; −7 to −1), and TG (−23 mg/dl; −46 to −1), and increased stimulated C-peptide (as insulin sensitizer; 0.93 ng/ml; 0.09–1.77) (see Figure 33 ). ( Gupta et al, 2001 ; Lu et al, 2008 ; Yaheya and Ismail, 2009 ; Ansari et al, 2011 ; Rafraf et al, 2014 ; Suchitra and Parthasarathy, 2015 ; Kaur et al, 2016 ; Singh et al, 2016 ; Verma et al, 2016 ; Ranade and Mudgalkar, 2017 ; Gholaman and Gholami, 2018 ; Kandhare et al, 2018 ; Hassani et al, 2019 ; Hota et al, 2019 ; Rashid et al, 2019 ; Hadi et al, 2020 ) Publication bias was detected in the funnel plot for HbA1c but not for FBG. In the funnel plot for HbA1c, there was an absence of smaller sized studies showing a larger positive effect, which could imply the effect may be larger than that reported from the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 34 shows the summary forest plot for Trigonella foenum-graecum (versus OAD). ( Singh et al, 2016 ; Najdi et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In clinical trials, on the other hand, consumption of Trigonella seed extract, enriched in 40% of furostanolic saponins for 30, 60, and 90 days, resulted in a 6.69%, 10.31%, and 21.98% reduction of FBG, respectively, a 13.7%, 20.6%, and 30.4% reduction in postprandial blood glucose levels, and a reduction in glycosylated hemoglobin levels (but not significant) [119]. In studies by Singh et al [120], 20 patients with type 2 diabetes took 5 mg of glipizide per day (Group A) for 12 weeks, 20 patients took 500 mg of fenugreek seed extract twice a day (Group B), and 20 patients took 2.5 mg of glipizide + 500 mg of fenugreek seed extract per day (Group C). In all groups, a significant decrease in FBG (A-33.97% > C-29.96% > B-24.62%) and glycated hemoglobin (A-12.98% > C-10.62% > B-9.38%) was observed; in Groups B and C, a significant decrease in TC (respectively: −5.66% and −3.87%), plasma triglycerides (−17.23% and −11.34%, respectively) and LDL cholesterol (−4.15% and −2.68%, respectively) could be noted.…”
Section: Fenugreek (Trigonella Foenum-graecum L)mentioning
confidence: 91%
“…The human trial showed a decrease in FBS range from 15 to 41 mg/dL, a decrease in HbA1C from 0.2% to 1.46% and HOMA-IR from 0.44 to 0.68. Singh et al [ 31 ] from India compared 500 mg fenugreek with 5 mg glipizide in 60 diabetes patients. The patients were randomized into three groups.…”
Section: Natural Products With Strong Evidence As Anti-hyperglycemic ...mentioning
confidence: 99%